Reducing bovine leukosis in dairy cattle - Smith, John F., 1962-; Stokka, Gerald L.; Scoby, R.K; Van Anne, T.; Shirley, John E. (Kansas Agricultural Experiment Station, 2011)
Bovine leukosis virus (BLV) is a cancerous condition of tissues in which lymph nodes and lymphocytes are affected. Infected cattle may be identified by testing blood sera for BLV antibodies using the agar gel immunodiffusion (AGID) test that requires 2 days for processing. Most dairy farms have infected animals, but the condition is not considered important because less than 1% of infected cattle show clinical signs. However, many of these cows are culled because of poor milk production or reproductive performance. Procedures for reducing and(or) eliminating the disease are outlined. Results obtained at the Kansas State University Dairy Teaching and Research Center demonstrate that feeding only colostrum and whole milk from BLV-negative cows to newborn and young calves is an effective method of reducing the incidence of BLV in future generations.
Keywords: Bovine leukosis; Virus; BLV- free colostrum